Peningkatan Aktivitas dan Hasil Belajar Siswa dengan Metode Jigsaw dan Media Tubuh Manusia pada Pembelajaran IPA di MTs. Negeri 4 Klaten Jawa Tengah - Binti Nashirotun (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to determine the increase in activity and science learning outcomes in human motion system material using the jigsaw method and human body media. This research method uses classroom action research. This research was conducted in class 8F MTs.N 4 Klaten in the 2019/2020 school year with 39 students as research subjects as science teachers and 8F grade students. The research instrument used test and non-test, while the data analysis used comparative descriptive analysis. The results of this study indicate that the use of the jigsaw method and human body media can increase student activity and learning outcomes in the human movement system material in class 8F MTs.N 4 Klaten.